Selenium and Human Health - M Abedi; MH Salmani Nodoushan; M Vakilli (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2013)
Introduction: Selenium is an essential element for human health and it is toxic at high concentrations. Selenium is a constituent component of selenoproteins that have enzymatic and structural roles in human biochemistry. Selenium is a best antioxidant and catalyst for production of thyroid hormone. This element has the key role in the immune function; prevention of AIDS progression and the deactivity of toxins. Furthermore, selenium is essential for sperm motility and can reduce abortions. Selenium deficiency was also associated with adverse mood states. The findings regarding cardiovascular disease risk related to selenium deficiency is unclear, though other conditions such as vascular inflammation, oxidative stress and selenium deficiency can cause this disease too. Moreover, consuming of 60 mg of selenium per day may be associated with reduction of cancer risk. In this study, a review of studies has been performed on the biochemical function of selenium toxicity, and its effects on human health. Furthermore, certain identified cancers associated with selenium have been discussed to absorb more attention to the status of this element and also as a guide for further studies. Selenium plays the dual character (useful and harmful) in human health, and then it is necessary to determine the concentration of this element in body fluids and tissues. An appropriate method for routine measurement of selenium in clinical laboratories is electro thermal atomic absorption spectrometry (ETAAS) with very low detection limit and good precision.